Locked up under lockdown: The COVID-19 pandemic and the migrant population - Ullah, AKM Ahsan (Social Sciences & Humanities Open, 2021)
Almost all countries in the world have now enforced coronavirus-related travel restrictions and border shutdowns. Migrant populations in the world are now considered the worst victims of COVID-19, and the spreaders too. This article aims to investigate the impacts that COVID-19 has on population migration. Informal interviews were conducted with the respondents who were stranded in different parts of the world via Skype and WhatsApp between February and November 2020. COVID-19 poses a threat to the millions who were caught between home and their final destinations – and are now living in overcrowded refugee camps where the terms ‘stay home’ ‘stay safe’ and ‘social distancing’ carries very little meaning.